Familial Mediterranean fever mutations are hypermorphic mutations that specifically decrease the activation threshold of the Pyrin inflammasome. (12th October 2017) - Jamilloux, Yvan; Lefeuvre, Lucie; Magnotti, Flora; Martin, Amandine; Benezech, Sarah; Allatif, Omran; Penel-Page, Mathilde; Hentgen, Véronique; Sève, Pascal; Gerfaud-Valentin, Mathieu; Duquesne, Agnès; Desjonquères, Marine; et al.
Abstract: Objectives: FMF is the most frequent autoinflammatory disease and is associated in most patients with bi-allelic MEFV mutations. MEFV encodes Pyrin, an inflammasome sensor activated following RhoGTPase inhibition. The functional consequences of MEFV mutations on the ability of Pyrin variants to act as inflammasome sensors are largely unknown. The aim of this study was to assess whether MEFV mutations affect the ability of Pyrin to detect RhoGTPase inhibition and other inflammasome stimuli. Methods: IL-1β and IL-18 released by monocytes from healthy donors (HDs) and FMF patients were measured upon specific engagement of the Pyrin, NLRP3 and NLRC4 inflammasomes. Cell death kinetics following Pyrin activation was monitored in real time. Results: Monocytes from FMF patients secreted significantly more IL-1β and IL-18 and died significantly faster than HD monocytes in response to low concentrations of Clostridium difficile toxin B (TcdB), a Pyrin-activating stimulus. Monocytes from patients bearing two MEFV exon 10 pathogenic variants displayed an increased Pyrin inflammasome response compared with monocytes from patients with a single exon 10 pathogenic variant indicating a gene-dosage effect. Using a short priming step, the response of monocytes from FMF patients to NLRP3- and NLRC4-activating stimuli was normal indicating that MEFV mutations trigger a specific hypersensitivity of monocytes to low doses of a Pyrin-engaging stimulus. Conclusion: Contrary to the NLRP3 mutations described in cryopyrin-associated periodic syndrome, FMF-associated MEFV mutations do not lead to a constitutive activation of Pyrin. Rather, FMF-associated mutations are hypermorphic mutations that specifically decrease the activation threshold of the Pyrin inflammasome without affecting other canonical inflammasomes.